2017
DOI: 10.3897/mycokeys.19.11161
|View full text |Cite
|
Sign up to set email alerts
|

A survey of xerophilic Aspergillus from indoor environment, including descriptions of two new section Aspergillus species producing eurotium-like sexual states

Abstract: Xerophilic fungi grow at low water activity or low equilibrium relative humidity and are an important part of the indoor fungal community, of which Aspergillus is one of the dominant genera. A survey of xerophilic fungi isolated from Canadian and Hawaiian house dust resulted in the isolation of 1039 strains; 296 strains belong to Aspergillus and represented 37 species. Reference sequences were generated for all species and deposited in GenBank. Aspergillus sect. Aspergillus (formerly called Eurotium) was one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…2006 ), indicating a strong relationship between species in sections Aspergillus and Restricti .) Quinolone Quinolactacin A1, Quinolactacin A2, Quinolactacin B Visagie et al. 2017 A. megasporus Chimeric echinulins and auroglaucins Cryptoechinulin B (= aurechinulin), (+) and (−)-cryptoechinulin D, 7-O-methylvariecolortide A, variecolortide A, (+) & (−) variecolortide B, (+) & (−) variecolortide C, (+) & (−) 7-isopentenylcryptoechinuline D, dihydrocryptoechinulin D, effusin A Gatti et al., 1976 , Inoue et al., 1977b , Li et al., 2010 , Wang et al., 2007b (misidentified as A. variecolor ); Kuttruff et al., 2011 , Yan et al., 2012 , Gao et al., 2012b (misidentified as A. effusus ), Gao et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2006 ), indicating a strong relationship between species in sections Aspergillus and Restricti .) Quinolone Quinolactacin A1, Quinolactacin A2, Quinolactacin B Visagie et al. 2017 A. megasporus Chimeric echinulins and auroglaucins Cryptoechinulin B (= aurechinulin), (+) and (−)-cryptoechinulin D, 7-O-methylvariecolortide A, variecolortide A, (+) & (−) variecolortide B, (+) & (−) variecolortide C, (+) & (−) 7-isopentenylcryptoechinuline D, dihydrocryptoechinulin D, effusin A Gatti et al., 1976 , Inoue et al., 1977b , Li et al., 2010 , Wang et al., 2007b (misidentified as A. variecolor ); Kuttruff et al., 2011 , Yan et al., 2012 , Gao et al., 2012b (misidentified as A. effusus ), Gao et al.…”
Section: Resultsmentioning
confidence: 99%
“…2013 (misidentified as A. effusus ), Chen et al. 2014 Aspergillus montevidensis , A. ruber Anthraquinones Catenarin, emodic acid, emodin (= parietin), erythroglaucin, fallacinol, physcion, questin (= emodin 8-O-methylether), questinol, rubrocristin, variecolorquinone A, (2S)-2,3-dihydroxypropyl-1,6,8-trihydroxy-3-methyl-9,10-dioxoanthracene-2-carboxylate, 3-O-(α-D-ribofuranosyl)questinol, 3-O-(α-D-ribofuranosyl)questin, rubrocristin, viocristin, isoviocristin, hydroxyviocristin, eurorubrin, asperinine A, B, ω-hydroxyemodin-5-merthyether, ω-hydroxyrubrocristin Anslow and Raistrick, 1940 , Bachmann et al., 1979 , Bachmann et al., 1982 , Anke et al., 1980a , Anke et al., 1980b , Fujimoto et al., 1999 , Engstrom et al., 1982 , Laatsch and Anke, 1982 , Arai et al., 1989 , Wang et al., 2006 (as Chaetomium globosum ), Smetanina et al., 2007 , Wang et al., 2007c (fungus misidentified as A. variecolor ), Du et al., 2008 , Wang et al., 2008 , Li et al., 2009 , Gomes et al., 2012 , Almeida et al., 2010 , Yan et al., 2012 , Du et al., 2014 , Micheluz et al., 2016 , Visagie et al., 2017 A. brunneus , A. chevalieri , A. cristatus , A. glaucus , A. intermedius , A. leucocarpus , A. mallochii , A. megasporus , A. neocarnoyi , A. niveoglaucus , A. pseudoglaucus , A. ruber , A. tonophilus (Citreorosein was reported from A. penicillioides by Micheluz et al. 2016 ) Asperflavins Anhydroasperflavin, asperflavin, asperflavin ribofuranoside, isoasperflavin Grove 1972a (misidentified as A. flavus ), Anke et al., 1978 , Fujimoto et al., 1999 , Li et al., 2006 (misidentified as Microsporum ), …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…were isolated from the mummy in one of the Archaeological museums in Zagreb [36]. Earlier studies identified the xerophilic fungi such as E. halophilicum, A. halophilicus, A. versicolor, Cladosporium spp., P.nalgiovense, P. milanense, P. brevicompactum, P. chrysogenum, P. nordicum, and P. polonicum were isolated from surfaces of dry-cured meat at minimum water content in locked environment [17,20,[37][38][39]. Xerophilic fungi such as A.…”
Section: Introductionmentioning
confidence: 99%
“…It was the aim of this review to revise the lists of producers of patulin, penicillic acid and moniliformin according to the most recent taxonomic treatments of the genera Aspergillus (Chen et al, 2016a(Chen et al, ,b, 2017Frisvad, 2015;Frisvad and Larsen, 2015;Hubka et al, 2015Hubka et al, , 2016Jurjevics et al, 2015;Kocsubé et al, 2016;Samson et al, 2011aSamson et al, ,b, 2014Samson et al, , 2017Sklenář et al, 2017;Varga et al, 2007aVarga et al, ,b, 2011aVisagie et al, 2014aVisagie et al, , 2017, Penicillium Houbraken et al, 2016;Visagie et al, 2014b) and Fusarium (Aoki et al, 2014;Burgess, 2014;Gerlach and Nirenberg, 1982;Lesley and Summerell, 2016;Nelson et al, 1983), as correct species-mycotoxin relations are important for prevention of mycotoxin formation in foods, feeds and biotechnological products.…”
Section: Introductionmentioning
confidence: 99%